Literary Translation behind Bars in the Late Soviet Union: Contextual Voices of Vasyl' Stus and Ivan Svitlychnyi - Savchyn, Valentyna (East/West)

(untitled) (Canadian Institute of Ukrainian Studies University of Alberta, 2021)
Translation in captivity is nothing new, nor is it restricted to a particular place or historical period. However, this social and cultural phenomenon is marked by a far more frequent occurrence in totalitarian societies. This article examines the practice of literary translation in Soviet labour camps, where, as a result of political repression, Ukrainian scholars, writers, translators, and lexicographers (aka prisoners of conscience) constituted a large part of the incarcerated population. The fact that translation activity thrived behind bars despite brutal and dehumanizing conditions testifies to the phenomenon of cultural resistance and translators’ activism, both of which deserve close scholarly attention. This study provides insights into practical, historical, psychological, and philosophical aspects of translation in extreme conditions. It seeks answers to the questions of why prisoners of conscience felt moved to translate, and how they pursued their work in situations of extreme pressure. Through the lens of translation in prison, the article offers a wide perspective on the issues of retranslation, pseudotranslation, translation editing, text selection, and the functions of literary translation. The focus of the paper is on Soviet Ukraine in the 1970s-80s, when a wave of political repressions led to the appearance of a new generation of prisoners of conscience. Case studies of Vasyl' Stus and Ivan Svitlychnyi are discussed, drawing on their letters during the incarceration period and the memoirs of their inmates.